Molecular aspects of skin aging. Literature review - Rogowski-Tylman, Michał; Narbutt, Joanna; Woźniacka, Anna; Lesiak, Aleksandra (Dermatology Review/Przegląd Dermatologiczny, 2016)
Skin aging is a complex process composed of sequential phenomena which lead to structural and functional changes. There are many pathways leading to photoaging, but their mechanisms are not well elucidated. Matrix metalloproteinases are a family of proteases known to degrade collagen. Aged skin is accompanied by higher metalloproteinase production, leading to degradation of extracellular matrix. Another pathway of aging is the complex TGF-β/Smad. Transforming growth factor-β is the primary regulator of collagen synthesis in skin. It has been reported that UV irradiation impairs TGF-β/Smad signaling through downregulating the transcription. In recent literature cathepsins and progerin are the newest proteins reported to be involved in aging. Cathepsins are a group of proteases with collagenolytic and elastinolytic activities, but their role in photoaged skin is only partially known. Progerin is an abnormal form of lamin A. In recent studies, it is noted for its participation in the process of skin photoaging.